The emergence of the occupation of district nursing in nineteenth century England - Denny, Elaine (1999)
This research examines the genesis of district nursing in England, and in particular explores the way in which district nursing became a paid occupation over the course of the nineteenth century. District nursing is defined as the care of the sick poor within their own homes, which is consistent with a nineteenth, rather than a twentieth, century meaning. At the beginning of the century an occupation of district nursing did not exist, yet by the end a formal occupation had emerged, and some associations of district nursing were attempting to create a profession which would attract educated women.